The Translation of a Savage, Complete - Parker, Gilbert, 1862-1932 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Translation of a Savage, Complete" by Gilbert Parker is a novel written during the late 19th century. The book delves into the themes of cultural clash and personal transformation, centered around the character of Frank Armour, who makes a fateful decision to marry Lali, an Indian girl, as a form of retaliation against his family's expectations. The story explores the complexities of their marriage and how both characters navigate their contrasting backgrounds. At the start of the novel, we are introduced to Frank Armour, who has just experienced heartbreak over the marriage of his former fiancée, Julia Sherwood. In a moment of impulsive bitterness, he marries Lali, a daughter of an Indian chief, in what appears to be a reckless act of defiance rather than out of true affection. As the narrative unfolds, Frank's family struggles to accept this new reality, with the impending arrival of Lali in England posing significant social challenges. The opening chapters portray a mixture of drama and irony, as the Armours grapple with their son's impulsive choices, setting the stage for the cultural and personal tensions that will arise throughout the story. (This is an automatically generated summary.)
Release date is 2004-11-16
Produced by David Widger
Keywords: Indians of North America -- Fiction; Married people -- Fiction; England -- Social life and customs -- Fiction